Polymer electrolyte fuel cell degradation - Mench, Matthew M; Mench, Matthew M.; Kumbur, Emin Caglan; Veziroğlu, T. Nejat (Amsterdam ; Boston : Academic Press, 2012)
For full market implementation of PEM fuel cells to become a reality, two main limiting technical issues must be overcome- cost and durability. This cutting-edge volume directly addresses the state-of-the-art advances in durability within every fuel cell stack component. [...] chapters on durability in the individual fuel cell components -- membranes, electrodes, diffusion media, and bipolar plates -- highlight specific degradation modes and mitigation strategies. The book also includes chapters which synthesize the component-related failure modes to examine experimental diagnostics, computational modeling, and laboratory protocol"--Back cover.
Includes bibliographical references and index.
Keywords: Fuel cells; Fuel cells -- Reliability; Polyelectrolytes